A Chaotic Masking Method based on Chaos Synchronization and Its Application - Nakagawa, Masahiro (Transaction of the Japan Society for Simulation Technology, 2024)
In the present work, we shall propose a simple chaotic masking model by means of the chaos synchronization of a globally coupled map (GCM) model with a sinusoidal mapping to involve a chaotic dynamics. In practice we shall present chaotic synchronization phenomena in GCM model by means of the Lyapunov spectrum analysis and put forward an iterative method to derive the invariant measure of the Frobenius-Perron equation. Then one obtains numerically the Lyapunov exponents under such a chaotic synchronization state. In addition one may confirm that the presently proposed chaotic synchronization model will be applied to a secured chaos masking scheme of an image of the standard image data base in terms of the encoding and the decoding processes. Through our computer simulations, it will be found that our chaotic masking model, which does not require any chaos feedback control in order to achieve synchronization between the transmitter and the receiver, may be considered to possess a capability to be applied to a highly secured communication technology.